2007
DOI: 10.1111/j.1467-8624.2007.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Dynamics Within Adolescent Friendships: Dyadic Mutuality, Deviant Talk, and Patterns of Antisocial Behavior

Abstract: Interpersonal dynamics within friendships were observed in a sample of 120 (60 male, 60 female) ethnically diverse 16- and 17-year-old adolescents characterized as persistently antisocial, adolescent-onset, and normative. Dyadic mutuality and deviant talk were coded from videotaped friendship interactions. Persistently antisocial adolescents demonstrated lower levels of dyadic mutuality compared with adolescent-onset and normative adolescents. Persistently antisocial and adolescent-onset adolescents spent more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
130
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 54 publications
9
130
1
3
Order By: Relevance
“…Although AFU and friendship quality also interacted for marijuana use persistence, this relationship was negative, such that AFU was stronger when friends were less close. A potential explanation for this lies in the "peer influence paradox," such that adolescents who tend to be strong socialization agents for more deviant behavior (e.g., illicit substance use) also tend to have poorer-quality friendships with others (e.g., Bagwell & Coie, 2004;Piehler & Dishion, 2007;Poulin et al, 1999). Conversely, there were also interactions between PFU and friendship quality for marijuana initiation and persistence, such that the effect of PFU increased as friends were closer.…”
Section: Variablementioning
confidence: 99%
“…Although AFU and friendship quality also interacted for marijuana use persistence, this relationship was negative, such that AFU was stronger when friends were less close. A potential explanation for this lies in the "peer influence paradox," such that adolescents who tend to be strong socialization agents for more deviant behavior (e.g., illicit substance use) also tend to have poorer-quality friendships with others (e.g., Bagwell & Coie, 2004;Piehler & Dishion, 2007;Poulin et al, 1999). Conversely, there were also interactions between PFU and friendship quality for marijuana initiation and persistence, such that the effect of PFU increased as friends were closer.…”
Section: Variablementioning
confidence: 99%
“…In other words, when conversations were sufficiently patterned to allow partners to reinforce antisocial utterances, the antisocial behavior was more likely to persist. A subsequent study indicated that these conversation dynamics applied to girls as well as boys (Piehler & Dishion, 2007 ).…”
Section: Exemplary Studiesmentioning
confidence: 99%
“…One of the most widely cited explanations of iatrogenic effects found in the evaluation of SEL programs is the negative effects of peer influences (Dishion & Kavanagh, 2003;Piehler & Dishion, 2007). In essence, this research suggests that peers learn negative behaviors from each other when instructed in groups.…”
Section: Discussionmentioning
confidence: 98%